MESIN PENCACAH PELEPAH DAN DAUN KELAPA SAWIT UNTUK PAKAN KAMBING DI DESA PUDING BESAR - Pristiansyah Pristiansyah; Nanda Pranandita; Muhammad Haritsah Amrullah; Hasdiansah Hasdiansah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2023)
In the process of raising goats, one of the factors that affect the process of goat growth and development is the availability of feed in the surrounding environment. In an effort to meet this availability, it is necessary to have a food source that is always available and usually comes from plants that exist in nature, such as grass or leaves. The availability of animal feed is not immune from the influence of weather conditions and the level of availability of weeds around it which are needed in large quantities. To deal with this, some farmers use alternative feed sources, one of which has been used is palm fronds and leaves and other organic waste. With the size of the palm frond which is quite large, it is necessary to chop it up so that it can be consumed directly by goats (Latifa S, Anto A, David S, Jeni W, Alexander Y). Of course, manual counting can be done, but it is not very effective and requires a lot of time and energy. Based on these problems, it is necessary to mechanization of the midrib and leaf counting process in order to facilitate the process. The purpose of science and technology for the community in this goat farmer group in general is to improve the quality and capacity of livestock production. In addition, by helping the availability of goat feed through the use of alternative feed sources other than the sources that have been available so far and applying appropriate technology for the process of chopping palm fronds and other organic waste. This machine is capable of chopping palm fronds and leaves with a maximum size of 2 cm. Based on the results of interviews with farmers, this size is a size that can be chewed or processed by goats when eating. Then, through this IbM activity, it is expected to be able to establish cooperation between partners and proposers from educational institutions. Partners can develop their business because the need for animal feed is more fulfilled through animal feed chopper machines, while institutions can directly apply science and technology and apply their knowledge into appropriate technology and can introduce Polmanbabel educational institutions more broadly to the community.